Representation of Power through Politeness Strategies in Bridgerton Season 1 Movie - Amalia, Nur Iva; Indah, Rohmani Nur; Bahtiar, Jessica Yunanda (Universitas Lancang Kuning, 2023)
Power can change how people act, how they think, what they do, and what policies they follow. People can reflect their power through the use of politeness strategies in their speech. This study aims to identify the types of politeness strategies and sub-strategies used in characters of Bridgerton Season 1 and explain how power is represented through politeness strategies. Its scenes and dialogue show qualities of decency and strength that need more exploration using the design of descriptive qualitative method. The pragmatic analysis in this study employed the theory of politeness strategy and the representation concept. The findings showed the use of bald on-record strategy, positive and negative politeness strategies, and off-record strategy. In addition, the representations of each strategy involved reflective, inflectional, and constructionist approaches. In the movie, the royal family, which includes kings, queens, princes, and their heirs, performed a symbol of power that plays a role in how power is used. Notably, the royal family serves as the show's symbol of power, highlighting its link to supremacy and authority. It implied that power is a sovereign thing based on authority and sovereignty. As the implication of this study, the future researchers should use sources of information that cover wider contexts.